Characterization of an archaeal virus-host system reveals massive genomic rearrangements in a laboratory strain - Mercier, Coraline; Thies, Daniela; Zhong, Ling; Raftery, Mark J.; Erdmann, Susanne (Frontiers in Microbiology, 2023)
Halophilic archaea (haloarchaea) are known to exhibit multiple chromosomes, with one main chromosome and one or several smaller secondary chromosomes or megaplasmids. Halorubrum lacusprofundi, a model organism for studying cold adaptation, exhibits one secondary chromosome and one megaplasmid that include a large arsenal of virus defense mechanisms. We isolated a virus (Halorubrum tailed virus DL1, HRTV-DL1) infecting Hrr. lacusprofundi and present an in-depth characterization of the virus and its interactions with Hrr. lacusprofundi. While studying virus-host interactions between Hrr. lacusprofundi and HRTV-DL1, we uncover that the strain in use (ACAM34_UNSW) lost the entire megaplasmid and about 38% of the secondary chromosome. The loss included the majority of virus defense mechanisms, making the strain sensitive to HRTV-DL1 infection, while the type strain (ACAM34_DSMZ) appears to prevent virus replication. Comparing infection of the type strain ACAM34_DSMZ with infection of the laboratory derived strain ACAM34_UNSW allowed us to identify host responses to virus infection that were only activated in ACAM34_UNSW upon the loss of virus defense mechanisms. We identify one of two S-layer proteins as primary receptor for HRTV-DL1 and conclude that the presence of two different S-layer proteins in one strain provides a strong advantage in the arms race with viruses. Additionally, we identify archaeal homologues to eukaryotic proteins potentially being involved in the defense against virus infection.